2012
DOI: 10.1111/j.1553-2712.2012.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Telephone Consults by Stroke Experts Supporting Community Tissue Plasminogen Activator Delivery

Abstract: Objectives Barriers to intravenous (IV) tissue plasminogen activator (tPA) use in ischemic stroke include limited treatment experience of community physicians. Models of acute stroke care have been designed to address these limitations by providing community support. These include support by telephone or televideo, with or without subsequent transport to tertiary care centers. The authors describe the frequency, characteristics, and effect of community phone consultations to a 24/7 stroke “hotline” staffed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
2
Order By: Relevance
“…It has previously been reported in uncontrolled reports of patients treated with intravenous tPA, 6,42,91,115 pretelestroke/ posttelestroke implementation evaluations, 131 comparisons between telemedicine-guided thrombolysis and in-personinitiated thrombolysis, 36,[120][121][122]132 and comparisons of telephone-and telemedicine-based thrombolysis. 36,133 Mortality after thrombolysis was reported as an outcome in a randomized trial of telephone and telemedicine acute stroke consultations, with no difference found between the modalities.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported in uncontrolled reports of patients treated with intravenous tPA, 6,42,91,115 pretelestroke/ posttelestroke implementation evaluations, 131 comparisons between telemedicine-guided thrombolysis and in-personinitiated thrombolysis, 36,[120][121][122]132 and comparisons of telephone-and telemedicine-based thrombolysis. 36,133 Mortality after thrombolysis was reported as an outcome in a randomized trial of telephone and telemedicine acute stroke consultations, with no difference found between the modalities.…”
Section: Mortalitymentioning
confidence: 99%
“…[127][128][129] Although telemedicine including video examination equipment is mentioned, it remains unclear how many patients treated with tPA were remotely assessed in the latter studies. Mortality at 90 days has been reported in a limited number of cohorts of uncontrolled studies and reports, 93,116 comparisons between telemedicine-guided thrombolysis and in-person-initiated thrombolysis, 99,119,124 an observational study of telephone versus telemedicine thrombolysis, 91 and 2 randomized controlled trials. 5,136 Longer-term mortality after thrombolysis by telestroke has been described for unselected stroke patients in an uncontrolled study, 117 pretelestroke/posttelestroke implementation evaluations, 131,137 and a comparison of hospitals within a telestroke unit network and matched conventional hospitals, 134,135 as well as 1 randomized controlled trial.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre os achados, a qualificação dos profissionais aparece, com muita ênfase, como aspecto fundamental para o funcionamento da programação estratégica de forma sincronizada (Brandão et al, 2022;Demaerschalk;Bobrow;Paulsen, 2008;Kapral et al, 2013;Kodankandath et al, 2017;López-Cancio et al, 2018;Majersik et al, 2012;Polivka;Polivka;Rohan, 2018;Sanossian et al, 2015;Whetten et al, 2018).…”
Section: Qualificação Dos Profissionais De Saúde Envolvidosunclassified
“…Em regiões escassamente povoadas (Majersik et al, 2012) ou em zonas rurais (Klingner et al, 2018;Majersik et al, 2012), há maior dificuldade em levar tecnologias como protocolos de roteamento, por exemplo.…”
Section: Obstáculos Ao Atendimento Em Redeunclassified